Trainee teachers’ readiness towards 21st century teaching practices / Norezan Ibrahim … [et al.] - Ibrahim, Norezan; Adzra’ai, Azzlina; Sueb, Rosilawati; Dalim, Siti Fairuz (Universiti Teknologi MARA Cawangan Selangor, 2019)
Teaching practicum is a component in preparing a student to be a beginner teacher. Yet there are a lot of preparations needed for the trainee teacher before he or she could teach in a school. A lack of preparation at the institution level could significantly affect trainee teachers’ readiness to teach in schools. Students who are not well-prepared for teaching assignments could became stressed due to high expectations from their supervisors. This study aimed to investigate the level of trainee teachers’ readiness and the challenges encountered during teaching practice. A total of 160 questionnaires were distributed to final year Education students who had completed their teaching practice. A descriptive research design was employed which utilized survey method to analyse teaching experiences of trainee teachers at the Faculty of Education, UiTM. The findings showed a high level of readiness among trainee teachers. An important finding from the data showed that students needed more individual attention be the most predominant challenge in teaching practice among the participants. This study sheds light into the crucial needs to help trainees teachers to raise the standard of teaching and to develop world-class teaching capabilities needed for classroom instructions in the 21st century millenium.